2019
DOI: 10.1016/j.joca.2019.02.391
|View full text |Cite
|
Sign up to set email alerts
|

Automatic knee cartilage and menisci segmentation from 3D-DESS MRI using deep semi-supervised learning

Abstract: Results:We found 4616 subjects with V00 MRI for both left and right knees. Due to missing WOMAC pain score, three subjects were excluded.The table includes the compartment markers with highest correlation to pain (rho > 0.15). These included cartilage quantity in the patello-femoral compartment and cartilage surface integrity markers in the tibio-femoral compartments. Also, internal structure markers for patellar cartilage and lateral meniscus were included. Finally, all Shape modes were included. Compartment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Atlas-based segmentation approaches are one of the most robust image-based segmentation techniques in the field of medical simulations, which perform classification and segmentation in one go, 42 although deep learning-based techniques also look promising. 35 In terms of generation of the model geometry, we compared earlier the results of the FE models obtained from the atlas-based approach and manually segmented knee joint models with experimental data. 32 In that study, we showed that the models based on the atlas-based approach were able to predict the progression of OA similar to the models based on manual segmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Atlas-based segmentation approaches are one of the most robust image-based segmentation techniques in the field of medical simulations, which perform classification and segmentation in one go, 42 although deep learning-based techniques also look promising. 35 In terms of generation of the model geometry, we compared earlier the results of the FE models obtained from the atlas-based approach and manually segmented knee joint models with experimental data. 32 In that study, we showed that the models based on the atlas-based approach were able to predict the progression of OA similar to the models based on manual segmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Panfilov et al. [94] used the GAN model based on U‐Net for the cartilage and meniscus segmentation. The U‐net architecture was modified to work as a generator which performed slice‐wise segmentation of 3D‐DESS MRIs.…”
Section: Knee Image Segmentation Approachesmentioning
confidence: 99%